Equivalent circuit modeling of ice exhibiting bound charge and quasi-dc behavior at –20⁰C to –60⁰C - Hassan, Jumiah; W. Yusoff, W. Mohamad Daud; Zainuddin, Hishamuddin; Abbas, Zulkifly; Grozescu, Ionel Valeriu; Khalid, Kaida (2005)
Measurement of the dielectric properties of ice at –20⁰C to –60⁰C in the frequency range of 10-2 to 106 Hz were done using the Chelsea Dielectric Spectrometer. Results obtained were fitted with a theoretical model, the equivalent circuit model. This model for ice exhibits a parallel combination of the quasi-dc process ε (ω )qd , the loss peak response lp ε (ω ) for the bound charge behavior and the response at high frequency ∞ ε . The relaxation peak shifted from 3 × 103 Hz at -20⁰C to 3 × 103 Hz at -60⁰C towards the lower frequency region as temperature decreases.